PERTALIAN ANALISIS SINTAKSIS PADA BENTUK WACANA BERTEKS JAWA - M Suryadi (Master Program in Linguistics, Diponegoro University, 2010)
To understand a word need the details comprehension of the unit of language such as sentences. However the complicated discourse start from and being in the unit of language itself, whether sentence as discourse component or discourse exponent. When the sentence as discourse component then the intention (the speakers aim will be delivered) and the binding capacity of sentence (the binding inter sentence in the discourse) that play role, when the sentence as discourse exponent so the interest (reality have been captured) play the role. If the three components (intention, interest, and the binding capacity of sentence) can be united in the unit of language so the effort of the speaker to develop his intelligence and his cooperation with the hearer can be tied in optimally